Method of Adaptability Assessment of an Intercept Missile in Challenging Marine Conditions - Zong-zhan SHAO; Yong XIONG; Wen-liu DAI (水下无人系统学报)
The main mission of an intercept missile equipped on surface warships is to intercept incoming anti-ship torpedoes as a hard-kill countermeasure. After the intercept missile receives the ignition signal from the system, the engine ignites and the body of the intercept missile flies out of the launching tube. When the missile enters water, the acoustic fuse completes separation process by igniting the suspension device to separate the missile body, and the air collar inflates and floats. Finally, the missile body starts to operate normally when it is stably suspended. Therefore, whether the launch, flight, and water-entering separation processes of the intercept missile are normal significantly affects its operational effectiveness. However, there are a series of practical problems concerning the intercept missile test in challenging marine conditions, such as difficulties in organizing and implementing testing, product recovery, and obtaining test data measurement. According to the technical characteristics and operating environment of the equipment, this paper proposes the performance requirements that should be satisfied when using the intercept missile. A comprehensive assessment method combining experimental verification and simulation calculations is proposed for the assessment. Studies regarding whether the attack angle, water-entering overload, and connector stress performance of the intercept missile can satisfy the requirements of challenging marine conditions are described. The results show that the intercept missile can meet the performance requirements of challenging marine conditions in the aforementioned three aspects. The findings can provide technical support for making evaluation conclusions on the adaptability of intercept missiles in challenging marine conditions.